Inhibition of α-Synuclein Aggregation and Mature Fibril Disassembling With a Minimalistic Compound, ZPDm - Peña-Díaz, Samuel; Pujols, Jordi; Pinheiro, Francisca; Santos, Jaime; Pallarés, Irantzu; Navarro, Susanna; Conde-Gimenez, María; García, Jesús; Salvatella, Xavier; Dalfó, Esther; Sancho, Javier; Ventura, Salvador (Frontiers in Bioengineering and Biotechnology, 2020)
Synucleinopathies are a group of disorders characterized by the accumulation of α-Synuclein amyloid inclusions in the brain. Preventing α-Synuclein aggregation is challenging because of the disordered nature of the protein and the stochastic nature of fibrillogenesis, but, at the same time, it is a promising approach for therapeutic intervention in these pathologies. A high-throughput screening initiative allowed us to discover ZPDm, the smallest active molecule in a library of more than 14.000 compounds. Although the ZPDm structure is highly related to that of the previously described ZPD-2 aggregation inhibitor, we show here that their mechanisms of action are entirely different. ZPDm inhibits the aggregation of wild-type, A30P, and H50Q α-Synuclein variants in vitro and interferes with α-Synuclein seeded aggregation in protein misfolding cyclic amplification assays. However, ZPDm distinctive feature is its strong potency to dismantle preformed α-Synuclein amyloid fibrils. Studies in a Caenorhabditis elegans model of Parkinson's Disease, prove that these in vitro properties are translated into a significant reduction in the accumulation of α-Synuclein inclusions in ZPDm treated animals. Together with previous data, the present work illustrates how different chemical groups on top of a common molecular scaffold can result in divergent but complementary anti-amyloid activities.